Pengelolaan Sains dan Teknologi di Pesantren - Irawan Irawan; Jenal Aripin; Tedi Priatna (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This paper aims to describe the management of science and technology in Islamic boarding schools. The method used in this research is qualitative. This research is a comprehensive data collection field study and pays attention to the relationship between data and the focus and research objectives. Data collection in this study used three techniques, namely (1) interviews, (2) observation: (3) library research. The results of this study indicate that the management of science and technology in Islamic boarding schools cannot be denied. The presence of science and technology in Islamic boarding schools can provide more benefits, because in addition to getting a touch of non-religious science and technology, the students also have good deepening of religion. Science and technology can also be the key to success in religious awakening. So pesantren must be prepared to face it. In fact, there are several Islamic boarding schools that have interacted with science and technology in Islamic boarding schools, and both of them have greatly influenced the style of education, one of which is the Tebuireng Science Boarding School (Trensains). Santri are invited to study religion (the Koran) as well as study the Kauniyah verses contained therein. Keywords: Management, Science, Technology, Islamic Boarding School